Jurnal Dinamika Administrasi Bisnis - Ardian, Asep Aan; Andayani, Sri; maduwinarti, ayun (Jurnal Dinamika Administrasi Bisnis, 2018)
Surabaya is an area have all kinds of cafe. Among many cafe in Surabaya one angkringan Jogja Mak Joss having decoration using the concept of ethnic Indonesian Java. So as to create a perception of different received by consumers Mak Joss Surabaya angkringan store.The purpose of this study to know the store atmosphere consumer perception of Java.            In this research using samples from 100 respondents with the accidental sampling and collecting data using a questionnaire.This is the kind of research quantitative. An analysis of the data used was the multiple linear regression analysis, correlation, determination, a partial and simultaneous. The results of the analysis shows that store atmosphere and perception buyers in angkringan Jogja Mak Joss Surabaya very attaching with the java and feel calm and comfort, Based on the conclusion of this analysis expected angkringan Jogja Mak Joss Surabaya can increase elements store atmosphere Java as general interior, exterior, store layout, the interior of display capable of influence the perceptions the purchase of those who are good in its implementation. Keywords: Store Atmosphere Java , General Interior , Exterior , Store Layout , The Interior Of Display , Consumer Perceptions